Knowledge and practice regarding menstrual hygiene among adolescent girls of rural field practice area of RIMS, Raipur (C. G.), India - Agarwal, Neerja; Soni, Nutan; Singh, S. P.; Soni, G. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Adolescent age group among girls have been recognized as a special period which signifies the transition from girlhood to womanhood. Menstruation is generally considered as unclean in the Indian society. Most of the adolescent girls had incomplete and inaccurate information about the menstrual physiology and hygiene as reported by many Indian studies. Very few authors have included the detailed aspects of the menstrual practices among adolescent girls. Methods: The current Community based cross sectional study was conducted by department of obstetrics and Gynaecology in connection with department of community medicine, Raipur Institute of Medical Science, Raipur (C.G), India. Among the adolescent school going girls in the field practice area of the Rural Health Unit and Training Centre during study period of 6 month from July 2017 to December 2017. 263 girls from the above mentioned schools, of the 8th and 9th standards, were selected for the study. Results: Majority of the school going adolescent girls belongs to 13 and 14 year of age. 50.95% , 21.67% and 12.93% girls reported that they had their menarche at the age of 13 year, 12 year and 14 year respectively. Majority of the girls were using cloth (49.81%) and only 17.87% were using sanitary napkins. Cleaning of external genitalia was not satisfactory in 32.70% of the girls. Only 58.17% girls used both soap and water for cleaning the genitalia. Pain in abdomen (59.70%) was found to be the most frequent complaint during menstruation. Conclusions: Knowledge on menstruation is sub-optimal and the practices are unacceptable for proper hygiene among study subjects. Menstrual hygiene is an important issue needs to be ensured.